Polska antropologia u schyłku XX wieku — kierunki i tendencje rozwoju jej społecznych funkcji - Drozdowski, Zbigniew (Polskie Towarzystwo Antropologiczne, 1988)
POLISH ANTHROPOLOGY TOWARDS THE END OF THE 20th CENTURY - DIRECTIONS AND TRENDS OF DEVELOPMENT OF ITS SOCIAL FUNCTIONS. Major trends of development of Polish anthropology were presented and its social functions with regard to the transformations of the Polish population.
POLISH ANTHROPOLOGY TOWARDS THE END OF THE 20th CENTURY - DIRECTIONS AND TRENDS OF DEVELOPMENT OF ITS SOCIAL FUNCTIONS